Analisis Pelaksanaan Walimatul ’Ursy Di Desa Koto Padang Sungai Penuh: Antara Tuntunan Syariah Dan Tradisi Masyarakat - Yusra, Hannilfi (BULLET : Jurnal Multidisiplin Ilmu, 2025)
This research is motivated by the issue of the high costs of conducting walimatul ‘urs in Koto Padang Village, Tanah Kampung District, Sungai Penuh City, which often becomes a financial burden, especially for families with limited economic conditions. This study aims to analyze the community's perceptions regarding the implementation of walimatul ‘urs in the village. The method used is qualitative, with data collection techniques through observation, interviews, and documentation. Data analysis was carried out through stages of data reduction, data presentation, verification, and conclusion drawing. The results of the study show that community perceptions are divided into two views. Some community members argue that the high costs of weddings reflect respect for the families of the bride and groom and the invited guests, thus becoming a symbol of social honor. However, some others believe that the high costs become a financial burden. Economically, the implementation of a wedding feast impacts the financial condition of both families. Psychologically, this event brings joy to the bride and groom. From a socio-cultural perspective, this tradition strengthens family ties and community solidarity. This study recommends strengthening Islamic education so that the wedding feast can be held more simply without diminishing the meaning of togetherness.